Tumor-promoting effect and tumor immunity of SRSFs - Zhang, Shuai; Zhang, Yongxi; Feng, Sijia; Han, Miaomiao; Wang, Zixi; Qiao, Dan; Tian, Jiaqi; Wang, Lan; Du, Baoshun; Zhang, Zheying; Zhong, Jiateng (Frontiers in Cell and Developmental Biology, 2025)
Serine/arginine-rich splicing factors (SRSFs) are a family of 12 RNA-binding proteins crucial for the precursor messenger RNA (pre-mRNA) splicing. SRSFs are involved in RNA metabolism events such as transcription, translation, and nonsense decay during the shuttle between the nucleus and cytoplasm, which are important components of genome diversity and cell viability. SRs recognize splicing elements on pre-mRNA and recruit the spliceosome to regulate splicing. In tumors, aberrant expression of SRSFs leads to aberrant splicing of RNA, affecting the proliferation, migration, and anti-apoptotic ability of tumor cells, highlighting the therapeutic potential of targeted SRSFs for the treatment of diseases. The body’s immune system is closely related to the occurrence and development of tumor, and SRSFs can affect the function of immune cells in the tumor microenvironment by regulating the alternative splicing of tumor immune-related genes. We review the important role of SRSFs-induced aberrant gene expression in a variety of tumors and the immune system, and prospect the application of SRSFs in tumor. We hope that this review will inform future treatment of the disease.